FINANCIAL MANAGEMENT SYSTEM'S EFFECTS ON GLOBAL ECONOMIC DEVELOPMENT PATTERNS - Ammar Neamah Awada; Anas Mahmood Ibrahim (American Journals, 2023)
study examines the effects of key global economic growth trends, such as globalization, financialization, fractionalization, intellectualization, and socializing, on the financial system as a management object. The main outcomes of this influence include the emergence of qualitatively new financial services, products, and instruments; modifications to the mechanisms and volumes of the delivery of financial services under conditions of increased financial risks, increased instability, and cyclical development of financial markets; and threats of global financial crises. Due to the imbalance of cash flows, the financial system's separability from other economic sectors, and the need to reorient financial flows for sustainable development and the pursuit of new standards for investment and financial efficiency activities of economic subjects in the "nature-production-society" system, it is difficult to bring the financial system into equilibrium. management into a true engine of the introduction of fresh concepts and innovations, and the effectiveness of reproductive processes.,The change in the conceptual underpinnings of the development of a new paradigm of financial management in the twenty-first century led to a conclusion. The main principles of the formation of the financial management system in the changing economy include the dominance of the value paradigm as the basis of value-oriented financial management, the priority of adaptive financial management of changes by cycle phases, recognition as the primary criterion for the effectiveness of maximizing operating cash flows, increasing the role of financial managers in resolving agency conflicts, and transformation of information, among others.
Keywords: financial system, financial management, global megatrends, value-oriented financial management.